Interrelation between population density and cancer incidence in the province of Opole, Poland - Chawińska, Ewa; Tukiendorf, Andrzej; Miszczyk, Leszek (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : In this study, we present the results of the interrelation between population density and cancer incidence in the Province of Opole, Poland. Material and methods: The material included demographic data from the Statistical Office in Opole and oncology information obtained from the Cancer Registry in Opole ‒ both research series encompass the five-year plan (years 2006–2010). A geostatistic analysis was performed using a spatial model (called the conditional autoregressive model). Based on the spatial regression coefficients, the strength of the relationship was measured in male and female populations, respectively. The statistical computations were performed in the Bayesian Inference Using Gibbs Sampling (BUGS) platform based on the so-called Markov Chain Monte Carlo (MCMC) technique. Results : The data presented in the study indicate that relative risk of cancer is higher within urban than in rural areas; an increase in population density of a thousand people per sq. km results in a 13% increase in risk of cancer among men and 16% increase in this risk for women.